A first preliminary study of the shallow water sponge fauna from Cyprus Island (Eastern Mediterranean) - Gabriele, Costa; Valentina, Giussani; Demetris, Kletou; Periklis, Kleitou; Maurizio, Pansini; Alexia, Setti; Roberto, Pronzato; Marco, Bertolino (Zootaxa, 2018)
Currently, more than 8,500 valid sponge species are reported in the World Porifera Database (http://www.marinespecies.org/porifera/) (van Soest et al. 2018). The Mediterranean Sea sponge fauna, counting almost 700 species, is one of the best documented in the world (Pronzato 2003; Pansini et al. 2011; van Soest et al. 2018) but the eastern part of the basin is by far less studied, in comparison with other Mediterranean areas (Pansini et al. 2000; Voultsiadou & Vafidis 2004; Topaloğlu & Evcen 2014). A small number of species, mainly belonging to the cosmopolitan genus Spongia (Dictyoceratida), are commonly used as bath sponges. Aim of this work is to provide further information on Cyprus Island sponges in general and on species that had commercial importance in the past.